STRATEGI REDAKSI FAJAR.CO.ID DALAM MENARIK PEMBACA DENGAN PENGGUNAAN CLICKBAIT PADA RUBRIK VIRAL (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research aims to find out the application of clickbait in the viral rubric at Fajar.co.id and the editorial policy regarding clickbait titles in Fajar.co.id's viral rubric. This research falls into the category of qualitative research by applying the case study analysis method. Data management and evaluation methods involve data reduction, presentation, and conclusion drawing. A document study is a data source that includes material from specific documents. In addition, the tools used in this study involved smartphones and laptops as test or validation tools. The number of informants involved in the context of this study was five people, consisting of four individuals from the Fajar.co.id website editing group (including a chief editor, two editors, and a reporter) and an expert informant who is also the Litigation Division of LBH Pers Makassar. The results showed that 1) The application of clickbait headlines in the viral section at Fajar.co.id has several concepts, namely, exaggeration, teasing, inflammatory, and the use of excessive punctuation in headlines. The application of clickbait in the rubric at Fajar.co.id clickbait is now a current demand because it is related to their income. 2). The editorial provisions regarding clickbait titles on viral rubrics at Fajar.co.id are that the editorial staff conducts news planning by discussing something viral on social media that directly gives the issue. Then, make a title that can attract readers while still following journalistic rules. Furthermore, reporters conduct coverage by looking for additional data on the issues being worked on from social media. From that planning, the reporter develops it into news.